2016
DOI: 10.1177/1474885116654389
|View full text |Cite
|
Sign up to set email alerts
|

A European Republic of Sovereign States: Sovereignty, republicanism and the European Union

Abstract: This article defends state sovereignty as necessary for a form of popular sovereignty capable of realising the republican value of non-domination and argues it remains achievable and normatively warranted in an interconnected world. Many scholars, including certain republicans, contend that the external sovereignty of states can no longer be maintained or justified in such circumstances. Consequently, we must abandon the sovereignty of states and reconceive popular sovereignty on a different basis. Some argue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 42 publications
0
40
0
Order By: Relevance
“…The second important commonality in the work of demoicrats is a tendency to justify this view of democratic legitimacy by appealing to freedom as non‐domination , a notion that lies at the heart of contemporary republicanism (Bellamy, ; Cheneval, , ch. 3; Nicolaïdis, , pp.…”
Section: Demoicracy Peoples and Non‐dominationmentioning
confidence: 99%
See 3 more Smart Citations
“…The second important commonality in the work of demoicrats is a tendency to justify this view of democratic legitimacy by appealing to freedom as non‐domination , a notion that lies at the heart of contemporary republicanism (Bellamy, ; Cheneval, , ch. 3; Nicolaïdis, , pp.…”
Section: Demoicracy Peoples and Non‐dominationmentioning
confidence: 99%
“…Demoicrats typically assume that in order to ensure the non‐domination of individuals, the states whose laws they are subject to must be democratic in the sense that those who regard themselves as a demos must make their own laws, exercising sovereign democratic authority. However, to be truly effective against domination, a state must itself not be dominated by other states or transnational forces that constrain domestic popular sovereignty (Bellamy, ; Laborde and Ronzoni, ; Nicolaïdis, , pp. 358–359).…”
Section: Demoicracy Peoples and Non‐dominationmentioning
confidence: 99%
See 2 more Smart Citations
“…The attraction of this view is twofold. 21 Yet, even among these there are different views on how EU decision-making is best structured; some argue in favour of a moralized mode of intergovernmentalism, 22 while others propose a model of a demoicratic confederacy. 17 On the other hand, in terms not dissimilar from Weiler's arguments, it is suggested that the idea of a demoicracy is normatively superior as it diffuses political allegiances 18 and thus abandons the exclusionary tendencies of a singular demos.…”
Section: The State Of the Literaturementioning
confidence: 99%